Acuracidade dos estoques a partir da triangulação prático-teórica - um estudo de caso na gestão da cadeia de sobressalentes no setor petrolífero offshore - Arruda, José Flávio Rangel de (2013)
This study examines the effectiveness of the supply chain inherent in operation and maintenance contracts (O&M) of turbomachinery installed in offshore units at Campos Basin (UO-BC), focusing on the spare parts management, in order to identify the main threats and opportunities to its efficiency, mainly marked by the level of accuracy of the spare parts records. Turbomachinery sector is in charge of significant portions of the exploration and production of oil and natural gas processes, which show substantial growth prospects in Brazil in the coming years, as a result of large investments of public and private initiatives However, the technical, logistical and legal peculiarities of its support structures, such as those applicable to its supply chain management, together with the typical occurrences of failures in inventory records, may present as obstacles to its efficiency. Therefore, through a representative case study, the research proposes to list the key elements for the characterization of a management system that considers the peculiarities and the potential opportunities and threats to the inventory accuracy, contributing to increasing the productivity and the competitiveness of the companies involved, reflecting in the availability of these strategic raw materials for the country. The thirteen consolidated key elements and the significant volume of academic references identified in different research approaches attest to the relevance and breadth of the subject, especially in the industrial sector